Respostas ecológicas de Plagioscion squamosissimus (Heckel, 1840) (Pisces, Sciaenidae) a uma seca supra sazonal como distúrbio em um reservatório do semiárido brasileiro - Souza, Antonia Elissandra Freire de (Universidade Federal Rural do Semi-Árido, 2016)
The aim of this study was to evaluate the ecological responses of Plagioscion squamosissimus on a supra-seasonal drought as ecological disturbance. Fishes were caught in the reservoir of Santa Cruz River basin Apodi / Mossoró, using gill nets with meshes of different size from February 2010 to November 2014. It was evaluated by the abundance of Capture per in Effort Unit biomass (CPUEb) and number (CPUEn), and through a one-way ANOVA and Tukey's test evaluated temporal variation. Calculated the Pearson correlation coefficients between the abundance and the accumulated rainfall and reservoir volume. Study the stomach contents were used the frequency of occurrence and volumetric methods and feeding index (IAI). To evaluate the variation of the niche and individual expertise was used proportional similarity index (PSI), present in RInSp package statistical software R. The condition factor of individuals was dismissed from the parameters of length-weight relationship determined by the equation: Wt = a Lpb. To assess differences in condition factor we carried out a two-way ANOVA followed by a Tukey test. It was registered a decrease in abundance as the reservoir level was decreasing, which is positively correlated with the volume of the reservoir, but not accumulated precipitation. P. squamosissimus diet consisted of shrimp, gastropod, plant material, fish, insects and shrimp larvae. Among the categories of items, the shrimp had the highest contribution in terms of frequency of occurrence and in volumetric. In 2010, 2013 and 2014 was recorded a higher frequency GR 0 (42.79; 37.77; 38.97). The proportional similarity index (PSI) showed high similarity between diet two individuals and the population, and individual expertise in November 2014. The highest average condition factor was obtained in 2012 and in the months May, found significant differences both between years and between months. The dry season above negatively affect the species by reducing the habitat area leading to reduction of their abundance. It is believed that the volume reduction causes major predator encounter rates with prey and this leads to an individual specialization trend. These results support the view that the dry cause changes in organisms
Keywords: Nicho trófico; Forrageamento; Dieta; Distúrbio; Barragem; CIENCIAS BIOLOGICAS::ECOLOGIA